The Expert Choice Implementation in Selecting the Electronic Voting Software - ., Faisal; Ridwan, Muhammad; ., Mardawati (International Journal of Engineering and Technology, 2018)
The voting service process conducted today is still done manually so that it becomes a decision to utilize the electronic voting. The electronic voting greatly reduces human control and human direct influence on this voting process. Problems faced by end users in the selection are there are so many choices of electronic voting software. Decision making, essentially a form of election of the various alternatives of action or multi-criteria decision making that can be selected. Decision support system in this research is used to select the type of electronic voting software. The method used in this research is the multi criteria decision making and analytical hierarchy process using expert choice software. And aims to make decisions that can make certain parties to take the best decision in choosing the type of electronic voting software. From the data processing is concluded that the first sequence is online voting 58.3%, express vote 17.2%, simply voting 17% and ballot online 7.5%. Processing of data obtained from the respondent expert inconsistencies value ratio is less than 0.1, thus the combined geometric calculation result data is fairly consistent.Â